Impacts of different photovoltaic panel technologies on electrical energy production and CO2 emission reduction - Iva Batić (Frontiers in Energy Research)
Given the increasing human population on Earth, there is a corresponding increase in the need for energy. One of the ecological and economical methods of meeting such energy needs is through renewable energy sources. Accordingly, this study analyzes the potential for producing electrical energy from solar radiation in Serbia. The Sun is the largest source of renewable energy, and Serbia has very good potential for utilization of solar radiation. In this work, we performed a comparative analysis of the electrical energy production from photovoltaic power plants using different photovoltaic panel technologies; these technologies affect not only the degree of conversion of solar irradiation to electrical energy but also the ecological parameters concerning the use of photovoltaic panels by reducing CO2 emissions. In this work, the following photovoltaic panel technologies are analyzed: monocrystalline, polycrystalline, thin-layer amorphous (a-Si), and cadmium–telluride (CdTe). The software tool used for the analysis was PVsyst.